The INoSIT (Integration Nature of Science in Inquiry with Technology) Model to Enhance the Scientific Literacy Skills of Junior High School Students: Development of Student Worksheet-Based Flip PDF Professional - Takda, Amiruddin; Balulu, Nasrun; Kasmiati, Sitti; Vaz, Benjamin Laurentino (STKIP Singkawang, 2024)
The research's goal was to create student worksheets based on the INoSIT model with the help of Flip PDF Professional that met the criteria for validity, applicability, and effectiveness to improve junior high school students' scientific literacy competence. The study adopted a research and development (R&D) design with a 4-D model. The student worksheets were tested at Junior High School 10 Kendari using one-group pretest-posttest design involving science teachers as observers. The research subjects for the limited trial were 15 students, and the extensive test was conducted with 27 students. Three validators provided personal validation of the student worksheets, which led to the collection of practicality data through observation sheets on the application of learning, student activities, teacher and student response questionnaires, and effectiveness data through science literacy test instruments. The research showed that the INoSIT model student worksheets fell into valid and reliable categories. For the limited and extensive trials, the n-gain <g> analysis results on measures of science literacy, like being able to explain scientific phenomena, were 0.632 and 0.712, respectively. This means that they were in the moderate to high category. Furthermore, regarding evaluating and designing scientific inquiries, the average normalized gain was 0.541–0.580, indicating an intermediate category. Similarly, on the indicators of interpreting data and scientific evidence, the average normalized gain was 0,510-0,572, indicating a moderate category. Based on this data, the INoSIT model student worksheets were considered practical and effective in improving the scientific literacy competence of junior high school students.